PRARANCANGAN PABRIK MAGNESIUM OKSIDA DARI BITTERN DAN BATU KAPUR KAPASITAS 30.000 TON PER TAHUN - , EDWARD ALEXANDER; , Dr.Ir. P. Sumardi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Magnesium oxide is made by heating up magnesium hydroxide so that the decomposition reaction of magnesium hydroxide into magnesium oxide and water would occur. Decomposition reaction occurs at a temperature of 900-1100oC and 4.5 atm of pressure. The equipment used to perform the reaction is rotary kiln. As the fuel, natural gas is used. While magnesium hydroxide obtained from the Mg2+ ion deposition process by adding a solution of calcium hydroxide. Solubility of magnesium hydroxide is smaller than that of calcium hydroxide so that magnesium hydroxide will precipitate. Considering the condition of the process, this plant is a low-risk type of plants. Designed production capacity of magnesium oxide is 30.000 tons per year. Gypsum byproduct of 13.990 tons per year. The need of utilities include 273.846ton/tahun of water, 277,014 tons / year of steam, 76,971 L / year of diesel, 37,600 m3/year compressed air. This plant requires a workforce of 168 people. The factory is planned to set up in Tuban, East Java . Area of land used is 4 hectares including residential and extension. Fixed capital requirements are U.S. $ 49,832,360 + Rp 53,845,399,044. Profit before tax earned Rp 105,902,085,694 and after tax is Rp 52,951,042,847. Working capital requirements are Rp 171,890,327,323. Percent return on investment (ROI) before taxes is 19.9% and 9.9% after tax. Pay out time (POT) before tax and after tax are 3.3 years and 5 years. Break even point (BEP) is 52.9% and shut down point (SDP) is 19%. Discounted cash flow (DCF) is 22.8%. From the results of economic evaluation, it can be concluded that the plant is quite interesting to set up.